EFFECT OF PULMONARY REHABILITATION ASSESSED BY CAT AND ITS RELATION TO ACTIVITY TOLERANCE - Luis Gaspar; Paula Martins; Fátima Gomes (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Chronic Obstructive Pulmonary Disease (COPD) is a common disease characterized by progressive airflow limitation, causing important functional impairment with repercussions on self-care. Previously characterized only by dyspnea, it is now recognized that a more comprehensive assessment is needed leading GOLD to recommend the COPD Assessment Test (CAT). Pulmonary Rehabilitation (PR) is the non-pharmacological treatment recommended in this context, and for that reason the goal of this investigation is to understand its effect on CAT as well as its relation with CF. Quasi-Experimental study that includes COPD patients admitted to PR and the impact of CAT and CF was assessed at the beginning and at the end of the PR program. Forty five patients were included (80% men), mean age 65.82 years and mean FEV1% of 40%. Statistical and clinically significant improvements were found (p < 0.001) in both CAT and CF, with a moderate negative correlation. We conclude that this PR program reduces symptoms and increases functional capacity in people with COPD.